Development and Characterization of Plant-derived Aristatoside C and Davisianoside B Saponin-loaded Phytosomes with Suppressed Hemolytic Activity - Ercelen, Sebnem; Bulkurcuoglu, Bunyamin; Oksuz, Mustafa; Nalbantsoy, Ayse; Sarikahya, Nazli Boke (Wiley-V C H Verlag Gmbh, 2024)
Saponins are glycosides widely distributed in the plant kingdom and have many pharmacological activities. However, their tendency to bind to cell membranes can cause cell rupture, limiting their clinical use. In the previous study, aristatoside C and davisianoside B were isolated from Cephalaria species. Cytotoxicity assays showed that they are more active on A-549 cell lines than doxorubicin but caused hemolysis. In the current research, aristatoside C and davisianoside B were loaded to phytosomes called ALPs and DLPs respectively, and characterized for particle size, zeta potential, encapsulation efficiency, release kinetic, hemolytic activity, and cytotoxicity on A-549 cell line. DLPs maintained the cytotoxic activity of the free saponins against A-549 cells with IC50 of 9,64 +/- 0,02 mu g/ml but dramatically reduced their hemolytic activity. Furthermore, temperature and time-dependent stability studies based on the size and zeta potential of ALPs and DLPs revealed that the phytosomes have sustained release properties over 2 weeks. Overall, DLPs displayed cytotoxicity against A-549 cells with minimal hemolysis and sustained release, highlighting their potential as nanotherapeutics for clinical applications. Phytosomal formulations of aristatoside C and davisianoside B compounds isolated from Cephalaria Aristata and Cephalaria davisina plants were prepared using the thin film hydration method. Physical characterization studies of the prepared phytosomal saponin formulation were carried out. The cytotoxic activity of phytosomal formulations was examined. The suppression of hemolytic activity of phytosomal formulations on erythrocytes caused by free saponins was investigated. image
Keywords: cancer; drug delivery; hemolytic activity; phytosome formulation; saponins